ER DER NOGEN NYHEDER? Sladder som etnografisk metode - Kongsbak, Tao (Tidsskriftet Antropologi, 2019)
Tao Kongsbak: Is There Any News? - Gossip as an Ethnographic Method Ethnographers have always used gossip in fieldwork. Malinowski was one of the first to point to the central importance of gossip in ethnographic data-collection. However, not many ethnographers have showed how they have actually and systematically used gossip as a method. The purpose of the article is to introduce gossip as an ethnographic method. Gossip is thus treated as a communicative genre, and some of the insights that can be generated through gossip are described: the social taste of the group, participants’ experience of intimate relations, core values of the group underlying the world view. This is followed by examples that show how to get involved in gossip. The article also comments on the widely discussed crisis of ethnographic authority and suggests that this crisis should be overcome, not by taking refuge in abstract theoretical concepts like „resonance" and „prophecy" but practically: the ethnographer must do more to involve himself with the locals and be more observant while he is involved. A systematic use of gossip in the field is one solution.